Stereotypes in Eka Kurniawan’s Short Story Collection Perempuan Patah Hati Yang Kembali Menemukan Cinta Melalui Mimpi - Sartika, Endang; Awaludin Nur Fauzi, M.; Okta Septiara, Agista; Nafiaturrahmah, Amalia; Setiyaningrum, Nabila (International Proceedings of Nusantara Raya, 2022)
Stereotypes are an idea or image that many people have toward other people, groups, or things which are usually dominated by negative beliefs. Stereotypes become part of the human mindset in terms of how to see other people from different perspectives. Stereotypes can be found in various media including movies, advertisements, and literature. This research attempts to analyze the stereotypes in Eka Kurniawan’s short story collection entitled “Perempuan Patah Hati Yang Kembali Menemukan Cinta Melalui Mimpi”. This short story collection appeals to our interest because of how Eka Kurniawan brought these stories into different places, plots, and topics. This research used a descriptive qualitative method in analyzing the stereotypes in the story. The data were collected through reading the stories, note taking or highlighting the stereotypes in the story, analyzing, then categorizing the stereotypes. This research found there are 4 types of stereotypes including nationality stereotypes, racial stereotypes, political stereotypes, and gender stereotypes. The result shows that the most dominant stereotypes in Eka Kurniawan’s short story collection are gender stereotypes.